Correlation of Physicochemical and Antimicrobial Properties of Liposomes Loaded with (+)‐Usnic Acid. Issue 5 (18th May 2020) - Battista, Sara; Bellio, Pierangelo; Celenza, Giuseppe; Galantini, Luciano; Franceschini, Irene; Mancini, Giovanna; Giansanti, Luisa
Abstract: (+)‐Usnic acid (UA) is a natural substance that displays pharmacological activity, but it is barely soluble in water, so it was included in liposomes in order to study its properties. First, the effects of phospholipid structure and loading methodology on UA entrapment efficacy were evaluated. Then, the physicochemical and biological properties (UA delivery efficacy to Staphylococcus aureus bacterial cells) of different liposome formulations containing structurally related amphiphiles derived from L‐ prolinol were fully investigated. Entrapment efficiency of UA with passive loading by incubation was 80–100 molar percentage, which is related to lipophilicity of the drug and to the packing and fluidity of the bilayer. Some of the investigated formulations show the potential of UA in delivery systems (minimum inhibitory concentration of liposomal UA: 8 μg/mL) and even subtle variations of the molecular structure of lipids can significantly affect the liposomes' physicochemical properties and efficiency of drug release. Abstract : Accelerated drug delivery : The physicochemical and biological properties of mixed liposomes were related to the molecular structure of their components: (+)‐usnic acid was included in mixed liposomes with high entrapment efficiency (80‐100 %) using passive loading by incubation with preformed liposomes. Formulation featuring the same zeta potential (13 mV) when loaded with (+)‐usnic acid showed different activity (toxic, ineffective or minimum inhibitory concentration of the drug equal to 8–16 μg/mL) against Staphylococcus Aureus .